1996
DOI: 10.1021/np960250m
|View full text |Cite
|
Sign up to set email alerts
|

HIV Inhibitory Natural Products. 26. Quinoline Alkaloids from Euodia roxburghiana

Abstract: Bioassay-directed fractionation of the CH2Cl2-MeOH extract of Euodia roxburghiana resulted in the isolation of two known quinoline alkaloids, buchapine (1) and 2, and three new furoquinoline alkaloids, roxiamines A, B, and C (3-5). Compounds 1 and 2 protected CEM-SS cells from the cytopathic effects of HIV-1 in vitro (EC50 0.94 and 1.64 microM, respectively), but 3-5 were inactive against HIV-1.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
66
0
2

Year Published

1999
1999
2022
2022

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 137 publications
(69 citation statements)
references
References 22 publications
1
66
0
2
Order By: Relevance
“…Extracts of M. lunu showed moderate test results. The ethanol and water extracts showed moderate activity and these results are in agreement with previous report by McCormick et al (1996). According to Wiart (2006), the leaf of P. bleo are simple spiral, glossy and succulent, it is believed to have anti-cancer, anti-tumour and antirheumatic also to treat diabetes and hypertension (Tan et al, 2004).…”
Section: Antibacterial Activity (Disc-diffusion)supporting
confidence: 90%
“…Extracts of M. lunu showed moderate test results. The ethanol and water extracts showed moderate activity and these results are in agreement with previous report by McCormick et al (1996). According to Wiart (2006), the leaf of P. bleo are simple spiral, glossy and succulent, it is believed to have anti-cancer, anti-tumour and antirheumatic also to treat diabetes and hypertension (Tan et al, 2004).…”
Section: Antibacterial Activity (Disc-diffusion)supporting
confidence: 90%
“…Previous studies on various Melicope species yielded interesting secondary metabolites including flavonoids, alkaloids, coumarins, and acetophenones (Fauvel et al, 1981;Parsons et al, 1994). M. ptelefolia is known to contain alkaloids of the quinoline, furoquinoline, pyranoquinoline types (Goh et al, 1990;McCormick et al, 1996) and benzopyrans (Kamperdick et al, 1997;Nguyen et al, 1998). It was reported that the leaves of M. ptelefolia exhibited antibacterial activity against Bacillus subtilis and Staphylococcus aureus (Rasadah and Zakaria, 1988).…”
Section: Introductionmentioning
confidence: 99%
“…5 In addition, they have been identified as novel antibacterials, as they present strong antibacterial effects on Staphylococcus aureus and Escherichia coli. 3 The continuous increase of isolable natural products as well as the pharmacological action of these quinolinediones has generated significant synthetic interest.…”
Section: Andmentioning
confidence: 99%